Optimization of PT Zhisheng Pacific Trading’s Digital Marketing Communication Strategy through Instagram Platform - Lesmono, Marselinus Michael Dendy (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Bisnis dan Informatika Kwik Kian Gie, 2024)
This research aims to explore the optimization of digital marketing communication strategies at PT Zhisheng Pacific Trading (MIXUE INDONESIA) through the Instagram platform in facing the era of the 4.0 and 5.0 industrial revolutions. The background of this study is based on the need for SMEs to adapt to changing consumer behaviors that increasingly rely on social media as a means of information and transactions. The research method employed is a descriptive qualitative approach, involving interviews with managers and employees of Mixue to gain an in-depth understanding of their digital marketing practices. The results indicate that effective use of Instagram significantly enhances brand visibility, consumer engagement, and product sales. Creative and interactive content, along with features such as Instagram Stories and paid advertisements, have proven capable of attracting the target audience's attention. The conclusion emphasizes that an integrated marketing communication strategy focused on sustained interaction with consumers through social media is crucial for business success in the digital era. This research provides guidance for SMEs to leverage social media's potential to enhance their competitiveness.